The Many Meanings of Vulnerability in the AI Act and the One Missing (TEST BioLaw Journal - Rivista di BioDiritto, 2024)
This paper reviews the different meanings of vulnerability in the AI Act (AIA). We show that the AIA follows a rather established tradition of looking at vulnerability as a trait or a state of certain individuals and groups. It also includes a promising account of vulnerability as a relation but does not clarify if and how AI changes this relation. We spot the missing piece of the AIA: the lack of recognition that vulnerability is an inherent feature of all human-AI interactions, varying in degree based on design choices and modes of interaction. Finally, we show how such a meaning of vulnerability may be incorporated into the AIA by interpreting the concept of “specific social situation” in Article 5 (b).
Keywords: Vulnerability; AI Act; AI; Human-Computer Interaction; Specific Social Situation